What school environment characteristics influence the physical fitness of low-income schoolchildren? - Douglas Eduardo Ferreira Maia; Rostand de Souza Lira Filho; Tércio Araújo do Rego Barros; Igor Rodrigues de Souza Sobral; Ana Beatriz Felix Lourenço; Nayara Souza de Oliveira; Paulo Felipe Ribeiro Bandeira; Marcos André Moura dos Santos; Thaliane Mayara Pessôa dos Prazeres; Rafael dos Santos Henrique (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Physical fitness (PF) is a key health determinant, linked to cardiometabolic risk, cognitive performance, and mental health.